2003
DOI: 10.1023/a:1024063726046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional status and pathophysiology of growth retardation in patients with phenylketonuria

Abstract: Recent European studies have shown that growth retardation is com-mon in people with phenylketonuria (PKU) during the first years of life while they receive a low-phenylalanine (Phe) diet. The aims of the present study were to assess the growth of our PKU patients and to search for nutritional and hormonal explanations for the growth delay. Twenty PKU patients aged 8 months to 7 years entered the study. The design was cross-sectional, a longitudinal study having already been performed in our centre. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 14 publications
2
44
0
Order By: Relevance
“…European studies [25-29] found similar growth retardation during the first years of life followed by restoration of the normal growth curve from the second year or later, supporting our results that 65.6% of the patients were under 10 years of age and all of them showed a significant catch up of growth at the follow-up study. In agreement with other authors, we found no correlation between phe levels and growth [24, 25, 30, 31]. However, it is clear that the outcome of growth in PKU patients depends on the therapeutic approach, genetic background and novel alimentary substitutes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…European studies [25-29] found similar growth retardation during the first years of life followed by restoration of the normal growth curve from the second year or later, supporting our results that 65.6% of the patients were under 10 years of age and all of them showed a significant catch up of growth at the follow-up study. In agreement with other authors, we found no correlation between phe levels and growth [24, 25, 30, 31]. However, it is clear that the outcome of growth in PKU patients depends on the therapeutic approach, genetic background and novel alimentary substitutes.…”
Section: Discussionsupporting
confidence: 92%
“…At the start of the study growth retardation was observed in our PKU patients in comparison with controls, like Dobbelaere (2003), who found his PKU patients shorter and lighter than the reference population [24]. European studies [25-29] found similar growth retardation during the first years of life followed by restoration of the normal growth curve from the second year or later, supporting our results that 65.6% of the patients were under 10 years of age and all of them showed a significant catch up of growth at the follow-up study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Even though medical formulas have improved in nutritional quality and palatability over the years, the severely restrictive diet necessary for the treatment of PKU still carries risk of associated nutritional deficiencies. There have been reports of growth retardation and specific deficits such as calcium, iron, selenium, zinc or vitamin D and B12 deficiencies [810]. Signs of osteoporosis may develop at an early age [11].…”
Section: Introductionmentioning
confidence: 99%
“…Adamczyk et al (15) reported normal MM only in those who adhered to their diet. Other studies reported no differences in MM, irrespective of diet compliance (19, 20). These conflicting results cannot be used in isolation to determine MM.…”
Section: Discussionmentioning
confidence: 85%